Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae) - Scalercio, Stefano; Infusino, Marco; Hausmann, Axel (Zootaxa, 2016)
In this paper, we describe Nothocasis rosariae sp. n. as the second European species belonging to the genus Nothocasis Prout, 1937. Differential features from its allopatric sibling species N. sertata (Hübner, 1817) are presented basing on wing pattern, morphology of male and female genitalia, and molecular data (COI barcode region). The type series is designated from southern Italy, but one examined specimen was collected in Epirus, Greece. The largest phenotypic and genetic variation was observed in the Pollino Massif, northern Calabria, whilst the population of the locus typicus in the Sila Massif, central Calabria, appears to be more homogeneous. 128 individuals were collected in mountainous beech forests from late August to mid-November. We hypothesize that larvae of N. rosariae sp. n. feed on Fagus sylvatica whilst those of its sibling species, N. sertata, feed on Acer.